TOURISTS’ PERCEPTIONS TOWARD THE SERVICE QUALITY OF TOURIST INFORMATION CENTER IN TORAJA - Rachel Rachel (UKI TORAJA, 2015)
Tourists’ Perception toward the Service Quality of Tourist Information Center in Toraja. Thesis. English Department. Teachers Training and Education Faculty. Christian University of Indonesia Toraja. The aim of this research is to know the level of tourists perception toward the servicequality of tourist information center (TIC) in Toraja.This research was conducted in Toraja. The data sources were primary source and secondary source. The writer used snowball technique to choose the sample. The data was analysed by using quantitative method. Library research and field reasearch were used to collect the data. In the field research, data was collected by using questionnaries distributed to the tourists who were trying the product in Tourist Information Center in Toraja. Based on the data analysed, shown that out of 20 variables, there are 9 variables that makes tourist felt very satisfied. There are 7 variable exist on the level satisfied and there are 4 variables in the level satisfied enough.The result of this research is the level of tourists ‘ perception toward the service quality of tourist information center in Toraja is generally satisfied.